Music Genre Identification Using SVM and MFCC Feature Extraction - Septian Yogi Yehezkiel; Yohanes Suyanto (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2022)
Indonesia  is a very diverse country because it has a vast territory and is occupied by millions of people from various tribe. Therefore, traditional music in Indonesia is also diverse because each region has its own culture and art.  In this study, the author used the Support Vector Machine(SVM) pattern recognition  to identify the Indonesian traditional music genre. This genre identification system is able to produce an accuracy of 83% using MFCC.Keywords : traditional music identification, Mel Frequency Cepstral Coefficient, Support Vector Machine.